Assessing E-Learning Agility in the Indonesian Public Sector - Pratiwi, Pratiwi; Krismiyati, Krismiyati; Wahyuadianto, Agus; Masrully, Masrully (KnE Social Sciences, 2022)
E-Learning has been used extensively in the public sector during the coronavirus pandemic. However, the lack of IT capability has led to irresponsive user experience measures. Agile bureaucracy is often mentioned as a set of values to respond to uncertainty during the robust demand of online interactions. Previous studies including systematic literature reviews have suggested that agile bureaucracy in the public sector is hindered by a culture of hierarchy and a lack of IT competency. Using empirical data that was derived from actual experiences, this study aimed to: 1) investigate participant perceptions of agility in e-learning for civil servants in Indonesia; and 2) recommend interventions to deal with the hinderances and prerequisites for agile bureaucracy in e-learning. This research collected data through open-ended interview questions and online surveys, and data were analyzed using the Atlas.ti software. This study considered several agile bureaucracy principles in e-learning, such as continuous improvement, collaboration, merit-based management, responsive and bottom-up decision making, and flexible support. The findings suggested that bottomup decision-making and competency-based human resource management were two critical challenges in agile e-learning provision. Further, this study recommends practical measures that can be taken by e-learning providers to solve these challenges. Keywords: agile bureaucracy, training, competency development, e-learning